Protection associated with a TB vaccine is linked to increased frequency of Ag85A-specific CD4+ T cells but no increase in avidity for Ag85A. Issue 38 (31st August 2016) - Metcalfe, Hannah J.; Steinbach, Sabine; Jones, Gareth J.; Connelley, Tim; Morrison, W. Ivan; Vordermeier, Martin; Villarreal-Ramos, Bernardo
Highlights: BCG-Ad5-85A protection was associated with higher CD4 + Ag85A-specific cell frequency. BCG-Ad5-85A protection was not associated with increased CD4 + Ag85A-specific avidity. BCG-Ad5-85A protection was not associated with epitope spreading. Abstract: There is a need to improve the efficacy of Bacille Calmette-Guérin (BCG) vaccination against tuberculosis in humans and cattle. Previously, we found boosting BCG-primed cows with recombinant human type 5 adenovirus expressing antigen 85A (Ad5-85A) increased protection against Mycobacterium bovis infection compared to BCG vaccination alone. The aim of this study was to decipher aspects of the immune response associated with this enhanced protection. We compared BCG-primed Ad5-85A-boosted cattle with BCG-vaccinated cattle. Polyclonal CD4 + T cell libraries were generated from pre-boost and post-boost peripheral blood mononuclear cells – using a method adapted from Geiger et al. (2009) – and screened for antigen 85A (Ag85A) specificity. Ag85A-specific CD4 + T cell lines were analysed for their avidity for Ag85A and their Ag85A epitope specificity was defined. Boosting BCG with Ad5-85A increased the frequencies of post-boost Ag85A-specific CD4 + T cells which correlated with protection (reduced pathology). Boosting Ag85A-specific CD4 + T cell responses did not increase their avidity. The epitope specificity was variable between animals and we found no clear evidence for a post-boost epitope spreading. In conclusion, the protection associated with boosting BCG with Ad5-85A is linked with increased frequencies of Ag85A-specific CD4 + T cells without increasing avidity or widening of the Ag85A-specific CD4 + T cell repertoire.